Pembentukan Karakter dengan Pendekatan Pembiasaan, Keteladanan, dan Pengajaran: Sebuah Kajian Literatur - Ainul Yaqin (Indonesian Journal of Humanities and Social Sciences, 2023)
Character education is a sine qua non condition for creating a good life. Students who have formed their character will be able to make themselves good citizens because they have a set of noble values needed in social interaction. Educational institutions have attempted to produce effective character education. However, the weak capacity of educators in understanding the workings of various educational approaches contributes to the failure to form character. In this study using a literature review approach, it is intended to answer the problem of how to work or the working principles of the character education approaches; habituation, modeling and teaching. The results of this study concluded that each of these approaches has a unique and distinctive way of working in shaping the character of students. Each approach also has an Islamic basis in shaping character. Of course, each has advantages and disadvantages, but educators must be able to place the proper use of these three approaches so that their effectiveness can be obtained.